(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
In this article, different approaches to organizing the independent work of students studying in higher educational institutions are considered. The article examines the method of studying the development of students of technical higher education institutions in the English language by translating scientific news and gives various recommendations.